The Advancement of Solid-State Transformer Technology and Its Operation and Control with Power Grids: A Review - Mollik M.S.; Hannan M.A.; Reza M.S.; Abd Rahman M.S.; Lipu M.S.H.; Ker P.J.; Mansor M.; Muttaqi K.M. (MDPI, 2023)
Solid-state transformer (SST) technology is one of the developing technologies that will be widely used in the future to integrate low-voltage and high-voltage networks with control circuitries and power electronics converters, facilitating renewables integration in smart grid applications. SST technology has crucial key advantageous features, including compact size and weight, low cost, and ease of connection in offshore applications. However, SST technology exhibits a few concerns, such as implementation, protection, economic, and communication compatibility, that need to be addressed. This paper aims to review SST technology with its advanced control schemes and provide future directions for research and development, applications, and prospects. In line with this, highly cited SST technology papers are examined to derive and summarize concerning issues related to its operation and control with further research development of power grids. Moreover, this review discusses the assessment and state-of-the-art technology of SSTs in different applications, focusing on configurations, control circuitry, and their drawbacks and benefits. Numerous issues and challenges of SST technology are explored to identify the existing knowledge gaps and potential future recommendations. All these critical analyses, information, and evaluations would benefit power engineers and researchers in developing and implementing advanced intelligent SST technologies for sustainable energy management in future power systems. 2022 by the authors.